Analisis Ekonomi Politik Liberal Klasik dalam Perspektif Kebijakan Publik di Indonesia - Marlita Jovita Sari; Eli Apud Saepudin; Diana Mahriva; Elda Azhani; Vani Putri Aryanto; Mochammad Luthfi Nabawi (UNIVERSITAS SERAMBI MEKKAH, 2024)
Classical Liberal Political Economy (EPLK) is an ideology that emphasizes the minimal role of the state in the economy and maximizes the role of the free market. This research analyzes how EPLK ideology influences public policy in Indonesia. This research uses qualitative methods with literature studies and policy analysis. The results show that EPLK has a significant influence on public policy in Indonesia, especially in the economic field. Policies such as deregulation, privatization, and trade liberalization have been implemented in Indonesia with the aim of promoting economic growth and increasing efficiency. However, this study also shows that EPLK can have negative impacts, such as income and wealth inequality, exploitation of labor and natural resources, and dependence on global markets. This study recommends that the Indonesian government carefully consider various factors in formulating appropriate public policies, including the positive and negative impacts of EPLK.